디지털 사이니지의 디자인 복잡성과 소구유형이 소비자 선호도에 미치는 영향 - 이현주(Hyun Ju Lee); 강기두(Gi-Du Kang); 이정규(JeongGyu Lee) (대한경영학회지, 2020)
디지털 사이니지는 공공장소 또는 상업적인 공간에서 다양한 정보를 네트워크를 통해 광고, 정보, 엔터테인 먼트, 미디어아트 등을 제공하는 디지털 미디어로서 이의 매체적 특성을 이해한 최적화된 사용자경험(user experience; UX)을 제공하는 것이 중요해지고 있다. 본 연구는 디지털 사이니지에서 제공하는 시각물의 디자인 복잡성(복잡/단순)과 소구유형(정보형/감성형)의 2원 상호작용에서 종속변수인 선호도에 미치는 영향을 미치 는지 알아보고자 하였다. 먼저 사전조사를 통해 독립변수인 디자인 복잡성의 정도를 ‘복잡, 단순’, 소구유형은 ‘정보형소구, 감성형소구’로 실험자극물을 도출하여 연구를 진행하였다. 연구결과는 선호도에 영향을 미치고 있으며 특히 디자인 복잡성이 단순하고 소구유형이 감성형인 경우 더 많은 영향을 미치고 있다는 것을 확인하였 다. 또한, 디자인 복잡성과 소구유형의 상호작용이 선호도에 미치는 효과는 플로우에 의하여 완전매개(complete mediation)가 아닌 보완적으로 매개(complementary mediation)되고 있음을 나타냈다. 이는 실험자극물인 저관 여 감성형 제품에 속하는 음료에 대한 전통적인 미디어에서의 선행연구에서 주로 보여진 연구결과들이 디지털 사이니지라는 매체에서도 일치하는 효과를 보이는지 실증적으로 확인한 연구로서 학문적인 시사점이 있다. 또한, 실무적 측면에서 제작 방향에 먼저 디자인 복잡성이 소비자의 선호도에 영향을 미치는 것을 인지하고 시지각물의 구성요소의 텍스트, 이미지, 레이아웃 등의 수량에 대한 조절이 필요하며 구성요소 일부분의 조정이 아닌 총합의 결과가 복잡성을 결정하므로 전체적인 측면에서 디자인의 ‘단순성’을 지향하여 제작해야 한다는 것이다. 또한, 소구방법의 선택과 메시지 문구를 결정함에도 주의를 필요로 한다. 이번 연구와 같이 초콜릿 음료는 감성형 메시지가 높은 효과를 얻을 수 있었던 것처럼 유사특성의 이미지를 제작할 때 감성에 호소하는 메시지를 담아 제작하는 것을 고려해야 한다. 이에 실무적 제작 이슈를 구체적으로 해소할 수 있도록 실증적 연구를 통해 더 나은 사용자 경험을 제공하는 제작 방향을 모색할 수 있었다. Digital signage plays an important role as digital media that provide diverse advertising and entertaining information, and media art through the network to public or consumers in the commercial places. It is becoming crucial in offering the optimized user experience (UX) such that it would be essential to understand its media characteristics. This study intends to identify the effect of the interaction between design complexity and appeal types from visual materials of the digital signage on consumers’ preferences using as the popular dependent variable in consumer behavior research. Conceptualizing the design complexity follows the previous study completed by Deng and Poole (2010) who defined the complexity based on the number of components in the promotion messages. The pre-test was conducted to verify the different level of design complexity (complex vs. simple), which would be utilized as a stimulus in the main study. Appeal types were selected based on the methods used by previous advertising research (Naylor, Kleiser, and Yorkston, 2008) as a moderator in this study. Appeal types were classified as information appeal and transformational appeal. Information appeal aims to stimulate consumers to assess clearly and logically the benefits of using products and services based on the factual information, whereas transformation appeal is designed to motivate consumers to make their choices based on their feelings combined with their past positive usage experiences. Specifically investigating the moderating effect of appeal types would help us look into deeper to verify how consumers interpret the information displayed on the digital signage differently depending on the design complexity when the message from the digital signage was perceived cognitively or emotionally. In this study, while information appeal was manipulated by displaying the promotion message which describes product attributes in detail, transformational appeal was manipulated by displaying the message which triggers consumers to recall their happiest moments of drinking sweet chocolate latte. The mediating variable, flow, was measured with the items developed by Jackson and Eklund (2002, 2004). 2 (design complexity: complex vs. simple) × 2(appeal types: informational vs. transformational) between-subjects factual design was used in this study. The participants were randomly assigned to one of the conditions. The result of the study showed that there was no effect of the appeal type when the design complexity was high. Conversely, we found that people showed higher preferences on the product promoted through the transformational type of the message when the design complexity of the digital signage was low. This study empirically confirms the findings from the previous studies on consumers’ attitudes toward the low-involved emotional products such as beverages. This research proves that people indicate consistent preferences on such products in the context of using digital signage. This research provides insightful managerial implication that marketing managers should choose the simple structure of the digital signage considering the layout, the amount of text information, and the product image when sending the emotional messages. This article was also able to seek a production direction that provides a better user experience through empirical research to solve the problems practically in production. KCI Citation Count: 0